The Influence of Work Life Balance, Digital Leadership, Employee Well-Being, and Work Flexibility on the Work Performance of Generation Z Employees with Job Satisfaction as a Mediating Variable in the Free Nutritious Food Program - Elmiano Artanto Epot Erong; M. Ilham Syahrul Qur’ani; Siti Mujanah; I Made Suparta (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of work-life balance, digital leadership, employee well-being, and work flexibility on employee performance with job satisfaction as a mediating variable in the Free Nutritious Meal Program (MBG) at the Nutrition Fulfillment Service Unit (SPPG) of Manggarai Regency.The research uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 120 Generation Z employees who were selected using purposive sampling techniques according to the research criteria. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through the SmartPLS application to test the validity, reliability, and direct and indirect relationships between variables. The results of the study show that work-life balance, digital leadership, employee well-being, and work flexibility have a positive and significant effect on job satisfaction and employee performance. In addition, job satisfaction has also been proven to have a positive influence on improving employee performance. In the mediation effect test, job satisfaction was only able to mediate the relationship between employee well-being and employee performance, while the relationship between work-life balance, digital leadership, and work flexibility on employee performance was not significantly mediated by job satisfaction. The findings of this study indicate that improving employee welfare, implementing adaptive leadership to digital developments, providing work flexibility, and creating a balance between personal and work life are important factors in increasing job satisfaction and performance of Generation Z employees in the Free Nutritious Meal Program. The results of the research are expected to be a reference for SPPG managers in designing more effective human resource management policies and oriented towards increasing organizational productivity.